Spatial differentiation characteristics and driving mechanism of rural-industrial Land transition: A case study of Beijing-Tianjin-Hebei region, China. (March 2021) - Xu, Mengyao; Zhang, Zhengfeng
Highlights: Construct theoretical models for rural-industrial land temporal-spatial transition. Identify spatial characteristics of the rural-industrial land transition. Rural-industrial land transition is positively related to socio-economic growth. Propose regulation strategies on transition paths for four transition patterns. Abstract: Given China's economic development, its rural areas have experienced rapid and profound transitions. In the Beijing-Tianjin-Hebei (BTH) region, these transitions have resulted in transition in rural-industrial land. Therefore, with rural-industrial land transition being the driving force behind rural economic growth, discerning its characteristics and driving mechanism could provide insights needed for guiding its regulation as well as determining suitable rural development paths. After constructing theoretical models for the rural-industrial land temporal and spatial transition in the BTH region, this study empirically analyzes the spatial differentiation characteristics and driving mechanism of rural-industrial land transition using object-oriented image analysis, the comprehensive index method, ArcGIS and FRAGSTATS landscape pattern analysis, and ordinary least squares and geographical weighted regression model. The results indicate that the high values of rural-industrial land dominant and recessive transition are distributed in the economically developed regions—Beijing-Tianjin and Handan—while undeveloped regions, such as Xingtai and Hengshui regions, show low values. Moreover, the high-value areas of the rural-industrial land transition index (RILT) are striped and the low-value areas are clustered. Furthermore, the spatial heterogeneity of rural-industrial land transition patterns is apparent. The transition coordination regions are located in the Beijing-Tianjin regions, the recessive lagging patterns are concentrated in the Langfang and Cangzhou regions, the dominant transition lagging regions are located in the Handan regions, and the transition lagging regions distributed in Xingtai and Hengshui regions. Finally, the results reveal that rural-industrial land transition is primarily driven by population, socio-economic, and location factors. For example, the degree of a rural-industrial land transition is positively related to socio-economic growth level. Thus, properly coordinating the relationship between these two is conducive to coordinating the BTH region's development, promoting regional rural revitalization and sustainable rural development in China. To facilitate this, targeted transition paths for different transition regions are therefore proposed.